Curriculum Innovation for Entrepreneurship Education: Developing Entrepreneurial Competencies in an Indonesian Entrepreneurship School - Kholilurrohman; Hiban Muharom; Ainun Lutfiya; Sutrisno (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2026)
Youth unemployment remains a structural challenge worldwide, and in Indonesia it is compounded by a persistent mismatch between graduate competencies and industry requirements. Islamic boarding schools (pesantren), as trusted community based educational institutions, are increasingly repositioned as incubators of entrepreneurial competence, yet the managerial dimension of their entrepreneurship curricula planning, implementation, and evaluation remains underexplored. This study examines how entrepreneurship curriculum management is enacted at Pesantren Wirausaha Kalasuba Indonesia (Pusaka Indonesia) to build santri (students') entrepreneurial competence. A qualitative case study design was employed, drawing on semi-structured interviews with the Education Department manager, educators, and santri, supplemented by observation and documentary analysis, and analyzed using the Miles and Huberman interactive model with source and method triangulation. Findings show that curriculum management is anchored in a 3H philosophy (Heart, Head, Hands) that balances character formation, critical reasoning, and practical skill. Planning is driven by need assessment; implementation combines differentiated, interest-based instruction with project based learning; and evaluation operates through a tiered Key Performance Indicator (KPI) system reinforced by reflective and deliberative practices. Limited professional human resources and uneven student readiness were the principal constraints, addressed through strategic partnerships and the optimization of internal human capital. The study contributes a values-integrated model of entrepreneurship curriculum management that extends conventional planning implementation evaluation frameworks by foregrounding spiritual formation as a core curricular dimension, offering a transferable reference for faith-based institutions designing entrepreneurship programs